A review on potential usage of industrial waste materials for binding heavy metal ions from aqueous solutions. (April 2016) - Ahmed, Md. Juned K.; Ahmaruzzaman, M.
Abstract: Presence of toxic and recalcitrant heavy metal ions in industrial effluents is a major environmental concern. These fatal metal ions are not only hazardous in exceeding concentrations but due to the property of biomagnification it is urgent to look for the plausible solutions. This review article is an attempt to gather the research findings attempted in yester years for the removal of such metals from aqueous solutions by using waste materials from industries, such as blast furnace sludge, slag and flue dust, fly ash, black liquor lignin, and red mud. Studies have been complied keeping various efficiency influencing parameters such as optimum dose, contact time, initial concentration of metal ions, and many more in consideration. This article also tries to summarize the various problems and shortcoming of the work carried so far and attempts to explore the feasible suggestions.